Treatment With LAU-7b Complements CFTR Modulator Therapy by Improving Lung Physiology and Normalizing Lipid Imbalance Associated With CF Lung Disease - Centorame, Amanda; Dumut, Daciana Catalina; Youssef, Mina; Ondra, Martin; Kianicka, Irenej; Shah, Juhi; Paun, Radu Alexandru; Ozdian, Tomas; Hanrahan, John W.; Gusev, Ekaterina; Petrof, Basil; Hajduch, Marian; et al. (Frontiers in Pharmacology, 2022)
Cystic fibrosis (CF) is the most common autosomal recessive genetic disease in Caucasians, affecting more than 70,000 individuals worldwide. It is caused by mutations in the gene encoding CFTR, an anion channel at the plasma membrane of epithelial and other cells. Many CF mutations disrupt the biosynthesis and trafficking of CFTR or reduce its ion channel function. The most frequent mutation, loss of a phenylalanine at position 508 (F508del), leads to misfolding, retention in the endoplasmic reticulum, and premature degradation. The therapeutics available for treating CF lung disease include antibiotics, mucolytics, bronchodilators, physiotherapy, and most recently CFTR modulators. To date, no cure for this life shortening disease has been found. Treatment with the Triple combination drug therapy, TRIKAFTA® benefits persons with CF (PwCF), improving their weight, lung physiology, energy levels, and overall quality of life. Nevertheless, elevated susceptibility to bacterial and viral infections and chronic inflammation persists. Concomitantly, FEV1 continues to decline although at a slower rate than without treatment. Our previous studies demonstrated that treating CF mice with fenretinide reduces inflammatory gene expression and improves their resistance to infection by Pseudomonas aeruginosa (P. aeruginosa). We also showed that LAU-7b, a clinical formulation of fenretinide, normalizes the lipid profile in CFTR-KO mice. The purpose of this study was to test if treatment with fenretinide can complement the efficacy of TRIKAFTA® that is now the standard of care for most patients. In this study, we examined the effect of combining LAU-7b oral treatment and Triple therapy combination on lung function in a F508deltm1EUR mouse model that displays lung abnormalities relevant to human CF. We assessed lung resistance, lung histopathology, protein oxidation, lipid oxidation, and fatty acid and lipid profiles in F508deltm1EUR mice. Treatment with combined LAU-7b and Triple therapy compared to Triple therapy alone resulted in improved lung physiology, histopathology, lipid oxidation, fatty acid profile, and correction of the very long chain ceramides/long chain ceramides ratio (VLCC/LCC) suggesting LAU-7b as a potential adjunct therapy.